2020
DOI: 10.3390/jpm10030131
|View full text |Cite
|
Sign up to set email alerts
|

Liquid lncRNA Biopsy for the Evaluation of Locally Advanced and Metastatic Squamous Cell Carcinomas of the Head and Neck

Abstract: Background: Long non-coding RNA (lncRNA) are RNA molecules that are more than 200 nucleotides long and have the ability to modify the activity of genes. They can be found in both healthy and cancer tissues, as well as in plasma, saliva and other bodily fluids. They can also be used as biomarkers of early detection, prognosis and chemotherapy resistance in several cancer types. Treatment of head and neck squamous cell carcinoma (HNSCC) patients with locally advanced disease is still difficult, and choice of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 69 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…The lincRNA regulator of reprogramming (lincRNA-RoR) is an oncogene involved in EMT along with drug resistance in different malignancies, e.g., NPC, BC, and HNSCC [142][143][144]. Interestingly, we have observed that its expression level increases after exposure to cisplatin [52]. One of the most poorly studied lincRNA is maternally expressed 9 (MEG9), speculated to be induced by hypoxia in a mouse model by Voellenkle et al [145].…”
Section: Known Lincrna Biomarkers In Hnsccmentioning
confidence: 94%
See 4 more Smart Citations
“…The lincRNA regulator of reprogramming (lincRNA-RoR) is an oncogene involved in EMT along with drug resistance in different malignancies, e.g., NPC, BC, and HNSCC [142][143][144]. Interestingly, we have observed that its expression level increases after exposure to cisplatin [52]. One of the most poorly studied lincRNA is maternally expressed 9 (MEG9), speculated to be induced by hypoxia in a mouse model by Voellenkle et al [145].…”
Section: Known Lincrna Biomarkers In Hnsccmentioning
confidence: 94%
“…Its up-regulation is associated with intensified tumor proliferation and migration along with a poor prognosis for ovarian cancer patients [127]. Moreover, we have also proved that high Emx2os expression levels can negatively affect progression-free survival (PFS) of individuals with HNSCC [52]. Growth arrest-specific 5 (GAS5) lincRNA was identified as a poorly conserved tumor suppressor that also acts as a decoy for the glucocorticoid receptor (GR) [47,128,129].…”
Section: Known Lincrna Biomarkers In Hnsccmentioning
confidence: 95%
See 3 more Smart Citations